Pendampingan Manajemen Pemasaran Produk Olahan Anggota PKK Desa Bangle Kec. Lengkong Kab. Nganjuk - Ali Anwar, Muhamad; Soim, Soim; Zakariya, Mukhamad; Subekan (Universitas Pangeran Diponegoro Nganjuk, 2022)
Marketing is one of the fundamental activities that need to be carried out by business actors, marketing activities include planning, pricing, promotion and distribution of goods or services that satisfy the needs of both existing and potential buyers. So that the marketing of